Trend Micro: Shifts in Underground Markets. Issue 6 (June 2020) - Unknown
Abstract : Malicious hacking and cybercrime have always been a more sociable activity than most people imagine. The popular image of a hoody-wearing teenager hunched alone over a keyboard in a darkened bedroom is a dangerously misleading cliché. Cybercrime is big business, often highly organised and revolves around communities.